2020
DOI: 10.1177/0748730420925573
|View full text |Cite
|
Sign up to set email alerts
|

Reduced VIP Expression Affects Circadian Clock Function in VIP-IRES-CRE Mice (JAX 010908)

Abstract: Circadian rhythms are programmed by the suprachiasmatic nucleus (SCN), which relies on neuropeptide signaling to maintain daily timekeeping. Vasoactive intestinal polypeptide (VIP) is critical for SCN function, but the precise role of VIP neurons in SCN circuits is not fully established. To interrogate their contribution to SCN circuits, VIP neurons can be manipulated specifically using the DNA-editing enzyme Cre recombinase. Although the Cre transgene is assumed to be inert by itself, we find that VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 53 publications
(94 reference statements)
2
23
0
Order By: Relevance
“…We have characterized and validated this line previously (Fan et al, 2015;Lee et al, 2015). Note that two recent studies report hypomorphic expression of VIP and/or AVP in Avp-IRES2-Cre (JAX #023530) and Vip-IRES-Cre (JAX #010908) mice (Cheng et al, 2019;Joye et al, 2020). The Vip tm1(cre)Zjh /J line (JAX #010908) originates from a C57BL/6 X 129S4/SvJae F1 hybrid background.…”
Section: Experimental Model and Subject Details Micementioning
confidence: 73%
See 1 more Smart Citation
“…We have characterized and validated this line previously (Fan et al, 2015;Lee et al, 2015). Note that two recent studies report hypomorphic expression of VIP and/or AVP in Avp-IRES2-Cre (JAX #023530) and Vip-IRES-Cre (JAX #010908) mice (Cheng et al, 2019;Joye et al, 2020). The Vip tm1(cre)Zjh /J line (JAX #010908) originates from a C57BL/6 X 129S4/SvJae F1 hybrid background.…”
Section: Experimental Model and Subject Details Micementioning
confidence: 73%
“…The AVP-Cre JAX #023530 line is also different from the AVP-Cre line used in our work (Pei et al, 2014). All Cre mouse driver lines reported here were used in the heterozygous condition, which did not affect circadian rhythm phenotypes, consistent with Cheng et al (2019) and Joye et al (2020). The mouse lines used in this work were backcrossed and maintained in a C57BL/6N background in order to maintain an isogenic background with the ES cells used for gene targeting (described below).…”
Section: Experimental Model and Subject Details Micementioning
confidence: 99%
“…Heterozygous VIP-Cre mice were used in our study. It is reported that the amount of VIP is reduced in VIP-Cre mice in the suprachiasmatic nucleus (Joye et al, 2020). To examine whether VIP expression in the OB decreased in VIP-Cre mice, we performed qRT-PCR analysis to detect VIP expression.…”
Section: Synaptic Properties and Odor Response Profiles Of Vip Intern...mentioning
confidence: 99%
“…Using conditional KO mice (Cre-LoxP system) comes with numerous potential caveats to consider in data interpretation [ 43 , [73] , [74] , [75] , [76] , [77] , [78] ]. We have recently further validated the effectiveness of the Synapsin cre -allele for inducing recombination of the Six3 flox -allele throughout the brain, including the SCN, PVN, and PeVN [ 25 ].…”
Section: Discussionmentioning
confidence: 99%